Association between red blood cell distribution width coefficient of variation and post-treatment bilirubin decline velocity in neonatal hyperbilirubinemia - Wei, Hongjuan; Zhang, Tingting; Ji, Rufeng; Tang, Yinyan (Frontiers in Pediatrics, 2025)
BackgroundRed blood cell distribution width coefficient of variation (RDW-CV) reflects erythrocyte heterogeneity, but its correlation with posttreatment bilirubin kinetics in neonatal hyperbilirubinemia (NHB) remains underexplored.MethodsThis cross-sectional study analyzed 803 neonates (≥35 weeks of gestation) with NHB. RDW-CV was measured at admission, and bilirubin decline velocity was calculated during phototherapy. Associations were evaluated using multivariate linear regression and restricted cubic splines, adjusted for demographic, maternal, and hematologic factors.ResultsEach 1% RDW-CV increase independently reduced bilirubin decline velocity by 2.04 μmol/(L·day) (β = −2.04, 95% CI: −3.48∼−0.60, P = 0.006). Compared with neonates in the lowest RDW-CV tertile (11.9 to <14.6%), those in the highest tertile (15.2%–20.8%) exhibited a significant reduction in bilirubin decline velocity of 5.33 μmol/(L·day) (β = −5.33, 95% CI: −8.44 to −2.21, P = 0.001). A linear dose–response trend (P = 0.001) was confirmed. Subgroup analyses confirmed consistent associations across neonatal sex, maternal age, and major pregnancy complications (all P for interaction > 0.05).ConclusionsRDW-CV is an independent predictor of bilirubin clearance in NHB, exhibiting a linear dose–response effect. These findings highlight its potential as a biomarker for phototherapy stratification.